Modification of a Carbon Paste Sensor with TiO₂ and ZnO Nanoparticles for the Cyclic Voltammetric Detection of Retinol - Ananta Adita Eka Putra; Pirim Setiarso (Jurnal Kimia Sains dan Aplikasi, 2025)
Retinol, a compound belonging to the retinoid group derived from vitamin A, is widely used in cosmetic formulations due to its proven efficacy in skin care. Analytical determination of retinol is commonly performed using conventional techniques such as HPLC and UV-Vis spectrophotometry. An alternative analytical method that offers potential yet remains underexplored is cyclic voltammetry. In this study, a cyclic voltammetry method for retinol analysis was developed using a modified carbon paste working electrode. The modification was done by adding ZnO and TiO2 nanoparticles to improve the electrode’s sensitivity. The sol-gel technique was employed to produce ZnO nanoparticles, which were then analyzed for their characteristics using several instruments, namely XRD, SEM, and FTIR. TiO2 nanoparticles were also subjected to characterization. The results of the study on ZnO nanoparticle synthesis demonstrated an average particle size measuring 30.5 nm. The optimum electrode composition was obtained at a ratio of 3:2:3:2 (Carbon: ZnO Nanoparticles: TiO2 Nanoparticles: Paraffin), producing an anodic peak current (IpA) of 4.58 × 10−3 A under optimum pH conditions at pH 7. As the generated peak current increases, the conductivity increases, as electron transfer for the reduction and oxidation processes becomes more facile. Applying this method to retinol analysis in brands X, Y, and Z facial serums yielded retinol contents of 0.00450 ppm, 0.00464 ppm, and 0.00427 ppm. The voltammetric method showed a LoD = 0.001029 ppm and LoQ = 0.003430 ppm, respectively. These results indicate that a ZnO and TiO2 modified carbon paste electrode is an effective tool for analyzing retinol by cyclic voltammetry.